Diversitas Bekicot di Kota Banjarbaru Kalimatan Selatan - Muhamat Muhamat (Universitas Lambung Mangkurat, 2009)
This study aims to quantify the dominance and diversity of snails in gardens around the Banjarbaru. Preliminary data snail populations used for further research related to the impact of snails as agricultural pests and public health. This research used the free collection. Species which was obtained by 4 namely Achatina fulica, Ampidromus adami, Hemiplecta humpreysiana, and Parmarion martesi.The highest diversity index found on the sugar garden and the dominant species A. fulica.